The Impact of Ayahuasca on Suicidality: Results From a Randomized Controlled Trial - Zeifman, Richard J.; Palhano-Fontes, Fernanda; Hallak, Jaime; Arcoverde, Emerson; Maia-Oliveira, João Paulo; Araujo, Draulio B. (Frontiers in Pharmacology, 2019)
Suicide is a major public health problem. Given increasing suicide rates and limitations surrounding current interventions, there is an urgent need for innovative interventions for suicidality. Although ayahuasca has been shown to target mental health concerns associated with suicidality (i.e., depression and hopelessness), research has not yet explored the impact of ayahuasca on suicidality. Therefore, we conducted secondary analyses of a randomized placebo-controlled trial in which individuals with treatment-resistant depression were administered one dose of ayahuasca (n=14) or placebo (n=15). Suicidality was assessed by a trained psychiatrist at baseline, as well as 1 day, 2 days, and 7 days after the intervention. A fixed-effects linear mixed model, as well as between and within-groups Cohen’s d effect sizes were used to examine changes in suicidality. Controlling for baseline suicidality, we found a significant effect for time (p <.05). The effect of the intervention (i.e., ayahuasca vs. placebo) trended toward significance (p = .088). At all time points, we found medium between-group effect sizes (i.e., ayahuasca vs. placebo; day 1 Cohen’s d = 0.58; day 2 d = 0.56; day 7 d = 0.67), as well as large within-group (ayahuasca; day 1 Cohen’s d = 1.33; day 2 d = 1.42; day 7 d = 1.19) effect sizes, for decreases in suicidality. Conclusions: This research is the first to explore the impact of ayahuasca on suicidality. The findings suggest that ayahuasca may show potential as an intervention for suicidality. We highlight important limitations of the study, potential mechanisms, and future directions for research on ayahuasca as an intervention for suicidality.